Forecasting of Utility Cost in a Deregulated Electricity Market by Using Locational Marginal Pricing - T. Mohanapriya; T.R. Manikandan; T. Venkatesan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In the deregulated electricity market bidding contest is the major operation. Prices obtained from the result of bidding strategy is essential, since all market participants do not be familiar with the accurate assessment of future prices in their decision-making process. Locational Marginal Pricing obtains from the Optimal Power Flow problem gives the economic value of electrical energy at each location. Proposed method is based on lossless DC Optimal Power Flow. To solve this LMP problem optimization based Linear Programming (LP) approach has been implemented. In this paper LMP values with transmission, line outage and generator outage constraints are studied. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7713